Accuracy evaluation of three electronic apex locators in teeth with immature apices - Bruno Martini Guimarães; Marcelo de Morais Vitoriano; Claudio Maniglia-Ferreira; Fabio de Almeida-Gomes; Marina Angélica Marciano; Clovis Monteiro Bramante; Marco Antonio Hungaro Duarte (Revista Sul-Brasileira de Odontologia, 2015)
The aim of this randomized controlled study was to evaluate the accuracy of Root ZX, iPex and YS-RZ-A apex locators in tooth with incomplete apices. Material and methods: Thirty human mandibular pre-molars without dental caries, fracture and with 1-3mm apical diameter and ¾ of root development stage were used. After coronal access, tooth length was determined with the visualization of a K-file, compatible with the root canal diameter, at the apex. To determine the root canal length using electronic methods, the teeth were included in alginate. The 30 teeth were measured with the three apex locators until achieving the apex foramen. During the measurement, the canals were inundated with 1% sodium hypochlorite. Statistical analysis was performed using Qui-square test (p < 0.05). Results: The Root ZX apex locator showed the higher accuracy (53.3%), with statistical difference in relation to iPex apex locator (33.3%) and YS-RZ-A apex locator (26.7%) (p < 0.05). Regarding the security limit of ±1 mm, the Root ZX apex locator did not show statistical difference in comparison with iPex apex locator (p > 0.05), but both were statistically different in relation to YS-RZ-A apex locator (p < 0.05). Conclusion: The results showed that all the studied apex locators were efficient in determining the root canal length in tooth with incomplete apex, considering the tolerance of ±1 mm. The Root ZX apex locator showed the highest accuracy with 100% of agreement.